Circadian expression of connexins in the mouse heart. Issue 4 (3rd July 2016) - Tong, Maoqing; Wang, Shuangshuang; Pang, Yuanyuan; Zhou, Ying; Cui, Hanbin; Ruan, Liemin; Su, Jia; Chen, Xiaomin
Abstract: Significant circadian variations exist in the frequency of cardiac arrhythmia; however, the underlying mechanism is largely unknown. Connexins are essential in the propagation of electrical activity throughout the heart and are an important determinant of conduction velocity. Their dysfunction is related to the genesis of cardiac arrhythmia. In this study, we investigated if cx40 and cx43 expressed circadianly in the mouse heart using suprachiasmatic nuclei (SCN) lesion and pharmacological autonomic nervous system block mouse. Significant 24-h variations were observed in the expression of cx40 and cx43 in the sham-operated mice. In the SCNX mouse, all genes examined lost circadian rhythm. In the ANSB mouse, the expressions of Bmal1 was dampened significantly but still had circadian rhythm, whereas the two connexin gene expressions lost rhythm. These results suggest that cx40 and cx43 gene expressions have clear circadian rhythm and might be regulated by the central clock in the SCN through the ANS.